The effects of aerogen-bonding on the geometries and spectral properties of several small molecular clusters containing XeO3. (10th October 2018) - Miao, Junjian; Xiong, Zhenhai; Gao, Yi
Abstract: Aerogen bonding, as a specific noncovalent interaction, has attracted wide attention recently. A number of theoretical studies have proposed this effect based on the analysis of electronic structures of aerogen-containing systems though, the spectral characteristics have not been identified, which becomes the obstacle for the experimental confirmation of this interaction. In this paper, we employed the density functional theory to explore the energetic and geometric properties, infrared, Raman spectra of five small molecular clusters XeO3 ·H2 O, XeO3 ·NH3, XeO3 dimer, XeO3 trimer, and XeO3 ·2H2 O. Our results show the binding energies of the most favorable conformations for the dimers are larger than  −10.00 kcal mol −1 and those for trimers are larger than  −20.00 kcal mol −1, which indicates the strong aerogen bonding is favorable for the stabilities of these clusters. More importantly, some new IR and Raman vibrations at fingerprint region (<1000 cm −1 ) are identified, which corresponds to the formation of aerogen bonds. This study provides a viable way for the experimentalists to characterize the aerogen bonding in future.